2008
DOI: 10.1161/hypertensionaha.107.099234
|View full text |Cite
|
Sign up to set email alerts
|

Added Impact of Obesity and Insulin Resistance in Nocturnal Blood Pressure Elevation in Children and Adolescents

Abstract: Abstract-The aim of the present study was to analyze the relationship between insulin resistance and the ambulatory blood pressure components in obese children and adolescents. Eighty-seven overweight and obese white children and adolescents of both sexes, of European origin from 6 to 18 years of age (mean age: 10.9Ϯ2.7 years), were selected. Obesity was defined on the basis of a threshold body mass index z score Ͼ2 (Cole's least mean square method) and overweight with a body mass index from the 85th to 97th p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
2
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 32 publications
5
55
2
5
Order By: Relevance
“…However, we found no associations between dipping and insulin sensitivity (S i ) or glucose metabolism (P-glucose, glycosylated hemoglobin Alc, disposition index or glucose efficiency). To our knowledge, there is only one study 9 that analyzed the association between dipping and insulin-glucose metabolism in obese, non-diabetic adolescents. Lurbe 9 reported higher sleep systolic BP, but not day:night ratio, among overweight and obese children with a high as compared with a low HOMA index.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we found no associations between dipping and insulin sensitivity (S i ) or glucose metabolism (P-glucose, glycosylated hemoglobin Alc, disposition index or glucose efficiency). To our knowledge, there is only one study 9 that analyzed the association between dipping and insulin-glucose metabolism in obese, non-diabetic adolescents. Lurbe 9 reported higher sleep systolic BP, but not day:night ratio, among overweight and obese children with a high as compared with a low HOMA index.…”
Section: Discussionmentioning
confidence: 99%
“…8 Among children, chronic poor glycemic control may place patients with type 1 diabetes at risk for higher nocturnal BP 4 and fasting insulin (fS-insulin) or HOMA is positively associated with sleep BP among obese children. 9 Obese, but otherwise healthy, adolescents are at higher risk of unfavorable glucose metabolism 10 as well as reduced nocturnal BP dipping 2 compared with normal-weight peers. However, there have only been few studies 9 analyzing the association between insulin-glucose metabolism, nocturnal dipping in obese and non-diabetic adolescents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in the salt-sensitive state, several risk factors are clustered together, leading to future cardiovascular events and renal failure. 20,21,26,[82][83][84][85][86] In our follow-up study 20 of essential hypertensive patients with known salt sensitivity, 31 cardiovascular events were documented during the follow-up period. Of these, 21 were stroke.…”
Section: Salt Sensitivity and Strokementioning
confidence: 99%
“…IR is a metabolic perturbation and seems to be related to endothelial dysfunction in normotensive offspring of subjects with arterial hypertension as well as in hypertensive patients. 30 Lurbe et al 31 found a strong relationship between IR, determined by HOMA and increased nocturnal blood pressure in a large cohort of obese children. Both, IR and elevated nocturnal blood pressure seem to be predictive of renal disease and cardiometabolic syndrome.…”
Section: Nocturnal Blood Pressure Regulates Endothelial Function T Komentioning
confidence: 97%